Design an Automatic Ph Controller Based on the Internet of Think - Tuwoso Tuwoso; Purnomo Purnomo; Syamsul Hadi (University of Merdeka Malang, 2022)
The pH level in pond water has a very important role for the life of the fish in it. Moreover, the pond water functioned as a medium for fish cultivation. Appropriate pH levels have many benefits for fish farming. One of them is to increase fish productivity. This study aims to develop appropriate technology that can be applied to pond water. The result obtained is the creation of appropriate technology in the form of an automatic pH controller based on the Internet of Think (IoT). In simple terms, the workings of the automatic pH controller are that the pH sensor will detect levels of hydronium ion exchange (H+) in pool water so that the sensor can determine the pH level in pool water, then data from the sensor will be received by Arduino and will be processed so that it can be visualized on the display. LCD. The existence of this technology is able to make catfish grow optimally, so that freshwater aquaculture ponds become more productive.